Extensive use of online social networks: a qualitative analysis of Iranian students' perspectives. (10th July 2019) - Akbari, Elham
In accordance with media dependency theory, the greater people's dependence on the media, the more important its role in their social lives. The research sample included 65 Iranian university students, with in-depth interviews used to collect data. The results demonstrated that students spent excessive time on online social networks, especially at the time of social and political events. Students perceived that these networks had both advantages and disadvantages. They argued that their belief systems were changing and that they faced new experiences. Moreover, a discrepancy was identified between Iranian users and users in other parts of the world in terms of their preferred social network and its function: Telegram was the most popular social network and none of the participants mentioned the educational function of these sites.